LncRNA SNHG1 promotes the development of oral cavity cancer via regulating the miR-421/HMGB2 axis - Liu, Jun; Zhao, Chaoyue; Yang, Song; Dong, Chen (Cellular and Molecular Biology, 2020)
Oral cancer (OC) is a common malignant tumor in oral surgery, which is prone to metastasis and the prognosis is not optimistic. Long-non-coding RNA (lncRNA) is a kind of endogenous transcripts with more than 200bp in length, lack of specific and complete open reading frame, and does not have the function of protein-coding. Studies have found that it can regulate gene expression at many levels, such as epigenetic level, transcriptional level and post-transcriptional level, thus affecting the occurrence and development of diseases. Recent studies have shown that the occurrence, development, of oral cancer, are associated with lncRNA. In this research, we found that lncRNA SNHG1 was up-regulated in oral cancer. Knockdown of lncRNA SNHG1 would inhibit the proliferation of oral cancer cells. Then we revealed a new mechanism that lncRNA SNHG1 regulated the growth of oral cancer via controlling the miR-421/HMGB2 axis, which provided new therapy for patients with oral cancer.